Palmitic Acid-Enriched Diet Increases α-Synuclein and Tyrosine Hydroxylase Expression Levels in the Mouse Brain - Schommer, Jared; Marwarha, Gurdeep; Nagamoto-Combs, Kumi; Ghribi, Othman (Frontiers in Neuroscience, 2018)
Background: Accumulation of the α-synuclein (α-syn) protein and depletion of dopaminergic neurons in the substantia nigra are hallmarks of Parkinson’s disease (PD). Currently, α-syn is under scrutiny as a potential pathogenic factor that may contribute to dopaminergic neuronal death in PD. However, there is a significant gap in our knowledge on what causes α-syn to accumulate and dopaminergic neurons to die. It is now strongly suggested that the nature of our dietary intake influences both epigenetic changes and disease-related genes and may thus potentially increase or reduce our risk of developing PD. Objective: In this study, we determined the extent to which a three month diet enriched in the saturated free fatty acid palmitate (PA) influences levels of α-syn and tyrosine hydroxylase, the rate limiting enzyme in dopamine synthesis in mice brains. Methods: We fed the m-Thy1-αSyn (m-Thy1) mouse model for PD and its matched control, the B6D2F1/J (B6D2) mouse a PA-enriched diet or a normal diet for three months. Levels of α-syn, tyrosine hydroxylase, and the biogenic amines dopamine and dopamine metabolites, serotonin and noradrenaline were determined. Results: We found that the PA-enriched diet induces an increase in α-syn and TH protein and mRNA expression levels in m-Thy1 transgenic mice. We also show that, while it didn’t affect levels of biogenic amine content in the B6D2 mice, the PA-enriched diet significantly reduces dopamine metabolites and increases the level of serotonin in m-Thy1 mice. Conclusions: Altogether, our results demonstrate that a diet rich in the saturated fatty acid palmitate can modulate levels of α-syn, TH, dopamine and serotonin which all are proteins and neurochemicals that play key roles in increasing or reducing the risk for many neurodegenerative diseases including PD.